Die Volksmenge vor einem zerstörten und geplünderten jüdischen Kleiderladen. Text auf der Rückseite - Stöcker, Alex,
Die Volksmenge vor einem zerstörten und geplünderten jüdischen Kleiderladen. Text auf der Rückseite.